Determination of Uranium Concentration in Human Urine at Al-Tuwaitha Region - Hamza, Hala M.; Hussain, Hayder S. (Iraqi Journal of Science, 2025)
In this study, 60 urine samples were collected from healthy volunteer individuals (both males and females) residing in the Tuwaitha region (aged 20-60 years) and compared with 30 urine samples from individuals living in another area of Baghdad, far from AL- Tuwaitha nuclear site (aged 20-60 years). The uranium concentration of these samples was measured using a solid-state nuclear track detector CR-39. The results indicated that the average uranium concentration for the Tuwaitha group was 0.507±0.032μg/L, which is higher than the permissible limits set by the World Health Organization, which is 0.3μg/L. While the uranium concentration for the control group was 0.267±0.045μg/L. The study also explored the relationship between uranium concentrations and gender, age, and smoking habits.